ESTIMATING HEDGING EFFECTIVENESS USING VARIANCE REDUCTION AND RISK-RETURN APPROACHES: EVIDENCE FROM NATIONAL STOCK EXCHANGE OF INDIA - Kaur, Mandeep; Gupta, Kapil (Copernican Journal of Finance & Accounting, 2020)
The present study examines hedging effectiveness of futures contracts in India by using variance reduction approach and risk-return approach by applying eight econometric models. It is observed that OLS hedge ratio generates highest hedging effectiveness using variance reduction approach, whereas Naïve hedge ratio generates highest hedging effectiveness using risk-return approach. Overall, it is observed that time-invariant hedging model generates superior hedging effectiveness as compared to time-variant hedging model.